Mathematical Literacy in Discovery Learning with Scaffolding Strategy Reviewed from Self Efficacy - Nugroho, Hartomo Adhi; mulyono, Mulyono; Hidayah, Isti (Unnes Journal of Mathematics Education Research, 2020)
The purpose of this study was to determine the quality of learning with Discovery Learning scaffolding strategies to students' mathematical literacy. This research uses mixed method research with embedded concurrent design of the method of research that combines the use of quantitative and qualitative research methods simultaneously or together but different weighting methods. The instrument used in this study in the form of instrument tests and interviews. Data analysis included data reduction, data presentation, draw conclusions and validity of the data. Mathematical literacy as measured in this study is limited to the domain that is communication, mathematising, representation, reasoning and argument, devising strategies for solving the problem of as, using symbolic, mathematics tools. Indicators to measure self efficacy, namely magnitude, strength, generality. The results showed that: (1) Learning Discovery Learning scaffolding strategy of good quality at the planning, implementation and evaluation of learning, (2) Students at a low self efficacy group can not achieve good indicator of mathematical literacy, namely communication, mathematising, representation, devising strategies for solving problems and using mathematics tools, reasoning and argument, and using symbolic, formal and technical language (3) Students who have medium self efficacy was can achieve good indicator of communication, mathematising, representation, devising strategies for solving problems and using mathematics tools, and reasoning and argument. But still there is a mistake in using symbolic, formal and technical language.(4) Students who have high self efficacy can achieve good indicator of communication, mathematising, representation, devising strategies for solving problems and using mathematics tools, and reasoning and argument.